Location Factors Impact the Career Choice of German Dental Practitioners - An Empirical Analytical Approach to Multi-Criteria Decision-Making - David Stein (SAGE Publishing, 2023)
Objectives In light of the increasing number of employed dentists and the decreasing rate of self-employed dentists, the factors that impact the decision to set up a dental office in Germany were investigated. Central to this approach is the provision of comprehensive dental care. Methods Using a pairwise comparison technique, the analytic hierarchy process (AHP), location factors identified as relevant in a systematic literature review and then prioritized by the professionals were weighted and ranked. Results According to this, five factors generally dominate the decision to open a dental office. These are, in descending order: environment for the family, quality of life in the private environment, real income, perception of location, and good infrastructure. The strongest impact on the rank order of the influencing factors is the socio-demographic characteristic of gender. For female dentists, the family environment is in the first place (p  =  .3196/C.R.  =  0.1502). For male colleagues, this influence ranks third (p  =  .1550/C.R.  =  0.1468) and real income receives the first place (p  =  .244/C.R.  =  0.1468). For female dentists, the influence of income ranks fifth (p  =  .076/C.R.  =  0.1502). Female and male dentists who grew up in rural areas were less likely to prefer employment (13.6%) than subjects of urban origin (40.2%). Conclusion The method of AHP is a way to map a priority list of all relevant factors. It can successfully show variations related to specific personal attributes. Obviously, there are factors that are of greater importance for the decision-making process to set up a dental office.